Effects of Karst Cave on the Stability of Diaphragm Walls During Ultra-Deep Excavation - Jiaer Mai; Zongtao Lin; Yanhong Wang; Ren Tang; Muyu Li; Benhai Lin; Wuzhang Luo (Advances in Civil Engineering)
Ultra-deep excavations in karst areas pose a substantial risk due to the presence of unknown karst caves. However, the literatures on deep excavations in karst regions remain limited and lack comprehensive discussion. This study investigates the effects of karst caves on the stability of the diaphragm walls (D-walls) during an ultra-deep excavation. A statistical analysis was conducted to examine the distribution of various parameters related to karst caves, including height, embedded depth, and roof thickness. It is revealed that these parameters follow a log-normal distribution. There is a strong probability (99.8%) that the embedded depth will exceed 10 m, a high likelihood (82.6%) of the height being under 6 m, and similarly, an 82.2% chance that the roof thickness will be less than 5 m. A three-dimensional finite element analysis was conducted to investigate the effects of the karst cave height, roof thickness, and location on the horizontal displacement of the D-walls. The results show that the karst cave have significant effects on the horizontal displacement of the D-wall, particularly at the bottom of the D-wall. Specifically, when the karst cave has a height of 6 m, a roof thickness of 1 m, and is located at a distance of 1 m from the wall, the horizontal displacement at the bottom of the D-wall can increase by 59 times compared with the condition without the presence of the karst cave. This severe increase in displacement results in a pronounced kick-in failure of the D-wall. The reason lies in the presence of the karst cave greatly reduces the bearing capacity of the bedrock within the foundation pit, thereby, rending it incapable of resisting the active earth pressure. The findings in this study can provide valuable references for formulating principles and treatment planes of the karst caves.